PENGOLAHAN LIMBAH KOTORAN AYAM PETELUR DI PETERNAKAN BANGUN REZEKI DESA TUNTUNGAN I KECAMATAN PANCUR BATU - Dian Nirwana Harahap; Sheila Fitriana; Nyaman Putra Bawamenewi; Linda Ewi Diana; Nana Mardiana (Universitas Islam Sumatear Utara, 2021)
The increasing need for food originating from animal protein such as meat and eggs indirectly increases the number of chicken breeders, especially layer hens, which also results in an increase in the amount of laying hens' waste. On the other hand, laying hens waste that causes an odor due to the ammonia gas, H2S (Hydrogen Sulfide), dimethyl sulfide, carbon disulfide, content contained in it causes losses to human health living around the farm and decreases the productivity of the livestock themselves. Bangun Rezeki Farm is one of the laying hens farms in Tuntungan I Village, Pancur Batu District, Deli Serdang Regency. Produces an average waste of 0.075 kg/head, meaning 540 chickens 40.5 kg/day. Imagine how the large amount of sewage produced from hundreds of laying hens that are not utilized. The purpose of this community service is to provide training to laying hens farm owners regarding how to process and utilize the laying hens waste into compost so that laying hens manure can be useful and have high economic value compared to not being used at all. The method of implementation stages carried out is starting from counseling, discussion, guidance and assistance to the process of making layer hens waste fertilizer to the owner of the Bangun Rezeki hens farm and the community around the village of Pancur batu, Deli Serdang by students and lecturers of Chemistry Education and Physics Education of FKIP UISU. This community service activity was carried out in August - December 2020 in Tuntungan I Village, Pancur Batu District, Deli Serdang Regency. It was attended by 10 participants from the community, lecturers and students. This community service activity produced 40 kg of compost from the processing of laying hens manure in a period of eight weeks until it could be packaged and ready to be sold. Compost from laying hens waste that has economic value is expected to be an additional source and increase people's income if managed seriously.